Great Mining Camps of Canada 6. Geology and History of the Wabana Iron Mines, Bell Island, Newfoundland - Pollock, Jeffrey C. (Geoscience Canada, 2019)
The Wabana iron mines were in operation from 1895 to 1966, during which time they produced over 80 million tonnes of iron ore. They are hosted by Early Ordovician rocks that contain Clinton-type stratiform ironstones. Mineralization is characterized by oölitic, dark red to purple-red to reddish brown beds of hematite-rich fossiliferous sandstone, siltstone, and shale. Three ironstone beds are of economic importance: the Lower (Dominion Formation), Middle (Scotia Formation) and Upper (Gull Island Formation) with the Lower bed extending over 3.8 km beneath Conception Bay. The iron content in all beds ranges from 45 to 61% with a silica concentration of 6 to 20%. Reports of iron on Bell Island go back to at least 1578, when a Bristol merchant reported retrieving ore samples for shipment to England. The deposits, however, remained undeveloped for over three centuries until their rediscovery by local fishermen in the late 1880s. In 1895, the Nova Scotia Steel & Coal Company acquired the mining lease for the claims and first ore was produced at surface from No. 1 mine in the Lower bed along the island’s northwest coast. By the turn of the twentieth century the Dominion Iron and Steel Company Limited acquired a share of the Bell Island claims, and with surface reserves exhausted, the decision was made by both companies to proceed underground and develop submarine mines. Over the next five decades mining operations were operated by several owners at a steady and at times an expanding rate, with periodic setbacks through two world wars and the Great Depression. The worldwide increase in demand for iron after World War II meant the mines were in full production and exporting over 1.5 million tonnes of ore per annum. In 1950, the unprofitable No. 2 mine was closed, and a series of major expansion projects were launched with the goal to double annual production to 3 million tonnes. By the 1960s, the Wabana mines faced increased competition from foreign producers, who flooded the world iron market with high-quality ore from low-cost open-pit deposits. The last mine at Wabana ceased operation in 1966 because the high-phosphorus content of the ore was incompatible with the newest steel-making technology and the market for Wabana ore all but disappeared. Over 35 million tonnes of ore was exported to Canada (Nova Scotia) while the remainder was shipped to the United Kingdom and Germany. At the time of closure, the Wabana mines were the oldest, continually producing mine in the country. Annual production peaked in 1960 when over 2.8 million tonnes of concentrated ore were shipped. Enormous potential reserves of several billion tonnes, grading 50% iron, remain in place beneath Conception Bay but the high cost of submarine mining and absence of a market for non-Bessemer ore present obstacles to any future re-development.